Matty Matheson : home style cookery - Matheson, Matty (Abrams, 2020)
Matty returns with 135 of his absolute favorite recipes to cook at home for his family and friends, so you can cook them for the people you love. Home Style Cookery is his definitive guide to mastering your kitchen, covering everything from pantry staples (breads, stocks, and pickles) to party favorites (dips, fried foods, and grilled meats), to weeknight go-tos (stews, pastas, salads), and special occasion show-stoppers (roasts, smoked meats, and desserts).